2014
DOI: 10.3892/ol.2014.2346
|View full text |Cite
|
Sign up to set email alerts
|

Elastography, a sensitive tool for the evaluation of neoadjuvant chemotherapy in patients with high-grade serous ovarian carcinoma

Abstract: The aim of the present study was to evaluate tumor stiffness by ultrasound elastography, which has the potential to provide additional information that is useful in predicting the response to neoadjuvant chemotherapy (NACT) in high-grade serous ovarian carcinoma (HGSC) patients. In total, 32 patients with International Federation of Gynecology and Obstetrics stage III and IV epithelial ovarian cancer treated with NACT underwent transvaginal and transabdominal sonography, followed by elastography and finally, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…We considered that the lesions of tubal pregnancy became soft, since parts of lesions were necrotic after MTX therapy. In a previous study, we had similar results in the study of neoadjuvant chemotherapy with ovarian high‐grade serous cancer . The trophocytes showed necrosis after MTX therapy.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…We considered that the lesions of tubal pregnancy became soft, since parts of lesions were necrotic after MTX therapy. In a previous study, we had similar results in the study of neoadjuvant chemotherapy with ovarian high‐grade serous cancer . The trophocytes showed necrosis after MTX therapy.…”
Section: Discussionsupporting
confidence: 67%
“…Although the colors indicating tissue elasticity in various studies were different, the principle of showing tissue stiffness was consistent. Our previous studies demonstrated it was effective and convenient …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 We reported several applications of elastography in gynecology in recent years, such as discrimination of high-and low-grade serous ovarian cancer, diagnosis of large-scar endometriosis, assessment of neoadjuvant chemotherapy in patients with high-grade serous ovarian carcinoma, and evaluation of the levator ani in women with pelvic organ prolapse. [4][5][6][7] However, to our knowledge, an evaluation of the regeneration process after cervical conization by transvaginal elastography in a clinical study has not been reported previously. In this study, we investigated the elastic properties of the cervix after cervical conization by elastography and its potential ability to predict future pregnancy.…”
Section: Abstract-cervix; Elastography; Gynecology; Transvaginal Ultmentioning
confidence: 99%
“…Also, another study which was performed with sonoelastography investigated the response of high- grade serous ovarian cancer to neoadjuvant chemotherapy revealed that tumour got stiffer after the treatment. 19 This also shows that malignant ovarian lesions are soft on elastogram but tissue stiffness increases after tumour treatment. Hence, benignity and/or response to treatment in an ovarian lesion is presented as hard elastogram pattern and increased strain index.…”
Section: Discussionmentioning
confidence: 92%